Ziarah: Mencari Satu Imaji dari Seribu Imaji-Nya : Sahabat, Imaji Kristiani - Antonio Julio Putra (FOCUS, 2021)
Pilgrimage is some act like make a devotional visit to sacred place. In there, we can find something which make us close with God. The way that we use to find it is we have to open one of part in ourself, that we called as intuition. From the intuition, people can examine some experience of pilgrimage, that is a experience of God. Pass through this experience will make something happened, that we called communication. From the communication, experience transform to be a image about The Transcendent. One of the thousand of The God Image can founded in this paper. That image appear because of a experience which bring the ratio and the faith, and then create some new perspective of The Transcendent